(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Purpose: To explore the presence of subtypes of intellectual functioning in children with mild intellectual disability (ID) and to externally validate the subtypes on measures of academic, adaptive and psychosocial functioning. Method: Participants were 167 children age 6-16 years with a mild ID. All children completed the WISC-III, WIAT, VABS, and PIC-R. Results: Based on a two-stage cluster analysis on the four WISC-III Index scores four subtypes emerged reflecting distinct profiles: (1) language-strength subtype; (2) nonverbal strength subtype; (3) symbol-processing strength subtype; and (4) global deficits subtype. The subtypes were externally validated on tests of academic achievement, adaptive functioning, and psychosocial functioning. Conclusions: Rather than only demonstrating a global or “flat” pattern of cognitive deficits, the findings suggest that children with mild ID have certain profiles of intellectual functioning that are similar to those seen in normal children and children with learning disabilities.